Tourism in Nepal: The Models for Assessing Performance of Amaltari Bufferzone Community Homestay in Nawalpur (Nepalese Journal of Development and Rural Studies, 2020)
This study assesses performance of Amaltari Bufferzone Community Home stay that received best homestay award in 2017. For the survey study, the data collected from 236 sample respondents were theorized based on social capital, ecotourism, asset-based community development and sustainability approach that are then supported by the empirical findings. An index was developed to describe the overall performance of the homestay by compositing five thematic indexes: relevancy, efficiency, effectiveness, impact, sustainability. The index value 92.65 from the range of minimum 48 and maximum 240 for the overall performance provides the strong quantitative evidence to answer the question “why did Amaltari receive the best award among”. The multiple regression model (R-square value 0.99) for overall performance also proves that independent variables describe the dependent variables by 99 percent. Among the independent variables relevancy and effectiveness indexes are more likely to describe dependent variable- theoverall performance index. The evidence shows that Amaltari hemostat has performed well due to the technical/financial supports of WWF, proper mobilization/utilization of conservation fund and homestay community fund, strong social capital, and quality leadership that has transforming the livelihoods of Tharu, Bote and Mushar indigenous people.However, they have some concerns like waste management in bufferzone areas, reviving the cultural organizations for preserving and transmitting culture from generation to generation, minimizing the modernization and demonstrative effects due to the excessive flow of the tourists and upgrading road connectivity.Hence, the local government, homestay and bufferzone users committee should collectively implement integrated tourism development programs for addressing such concerns.